Coupling high frequency monitoring and bioassay experiments to investigate a harmful algal bloom in the Bay of Seine (French-English Channel). (July 2021) - Serre-Fredj, Léon; Jacqueline, Franck; Navon, Maxime; Izabel, Guillaume; Chasselin, Léo; Jolly, Orianne; Repecaud, Michel; Claquin, Pascal
Abstract: Coastal ecosystems are increasingly threatened by eutrophication and dystrophy. In this context, the full pattern of a bloom dominated by the dinoflagellate, Lepidodinium chlorophorum, was investigated by a high frequency monitoring buoy equipped with sensors allowing nutrients and photosynthesis measurements. An increase of the N/P ratio affected phytoplankton physiology leading to bloom collapse with a slight oxygen depletion. In parallel, enrichment experiments were performed on the natural bloom population. After 5 days of incubation the community structure, using flow cytometry and several physiological parameters were analysed. The data reveal a potential N and P co-limitation and a decoupling between primary production and productivity in fully enriched conditions. Under unbalanced N/P inputs, high level of alkaline phosphatase activity and transparent exopolymeric particle production, which favour phytoplankton sedimentation, were observed. Nutrient inputs and their stoichiometry control phytoplankton growth, the community structure, physiological regulations, the fate of the bloom and consequences. Graphical abstract: Unlabelled Image Highlights: Lepidodinium chlorophorum harmfull algal bloom fully monitored at high frequency Triggering and fate of the bloom explore with nutrients and photosynthetic HF data P limitation cause the bloom decline as flagged by the Fv/Fm and N/P ratio. Enrichment experiment reveal potential N and P co limitation. High TEP production under N or P limitation in enrichment experiment